All‐Ambient‐Processed CuSCN as an Inexpensive Alternative to Spiro‐OMeTAD for Perovskite‐Based Devices. Issue 1 (17th November 2020) - Asuo, Ivy M.; Bouzidi, Soraya; Ka, Ibrahima; Rosei, Federico; Pignolet, Alain; Nechache, Riad; Cloutier, Sylvain G.
Abstract : Organic hole‐transporting materials (HTM) are widely used for high‐efficiency solar cells. However, compared with their inorganic counterparts, these materials are often expensive and require complex synthesis methods and the addition of costly dopants to improve their performance. In addition, exposure to the ambient environment affects the chemical stability of some organic materials as well as their device characteristics. Herein, an all‐ambient fabrication method is used to develop a CuSCN layer as an alternative to the conventional Spiro‐OMeTAD HTM. CuSCN thin films are incorporated into both solar cells and photodetectors to study their effect on the optoelectronic properties of these devices. For the solar cells made with CuSCN, a power conversion efficiency of 14.3% is achieved, with remarkable ambient‐stability without encapsulation. Regarding the photodetectors with CuSCN, high‐specific detectivity up to 10 12 Jones is exhibited. Solution‐processed devices exhibit overall impressive performances and represent an essential step toward large‐scale fabrication of efficient, stable, facile, and inexpensive perovskite‐based optoelectronic technologies. Abstract : The integration of copper (I) thiocyanate as a hole‐transporting layer could be beneficial for efficient, stable, and notably, low‐cost all‐ambient‐processed perovskite‐based devices.